2017
DOI: 10.1111/jeb.13034
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis reveals that cryptic diversity is linked with habitat but not mode of life

Abstract: The ubiquity of genetically distinct, cryptic species is limiting any attempt to estimate local or global biodiversity as well as impeding efforts to conserve species or control pests and diseases. Environmental factors or biological traits promoting rapid diversification into morphologically similar species remain unclear. Here, using a meta-analysis of 1230 studies using DNA sequences to search for cryptic diversity in metazoan taxa, we test two hypotheses regarding the frequency of cryptic taxa based on mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 54 publications
2
21
0
3
Order By: Relevance
“…Also, the number of markers, the number of sequences and the number of base pairs generally correlate positively with each other across studies, for both mitochondrial and nuclear genes (see Poulin & Pérez-Ponce de León, 2017). Therefore, we use only the number of sequences to control for study effort in subsequent analyses, since the number of cryptic species found tends to increase with the level of effort put into their search (Poulin, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the number of markers, the number of sequences and the number of base pairs generally correlate positively with each other across studies, for both mitochondrial and nuclear genes (see Poulin & Pérez-Ponce de León, 2017). Therefore, we use only the number of sequences to control for study effort in subsequent analyses, since the number of cryptic species found tends to increase with the level of effort put into their search (Poulin, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…genetically distinct but morphologically similar species, are extremely common among all higher taxa (Bickford et al, 2007). When correcting for study effort and accounting for other confounding variables, cryptic species do not appear to be more frequent among parasitic than free-living taxa (Poulin & Pérez-Ponce de León, 2017). Yet cryptic parasite species are reported with increasing frequency; this is a consequence of genetic methods having become standard practice for parasite identification, and often being used deliberately to prospect for cryptic diversity (Blouin, 2002;Locke et al, 2010;Rosas-Valdez et al, 2011;Razo-Mendivil et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Martin, Gido, Bello, Dodds, & Veach, 2016). To take SIPD into account in general conservation policy and local conservation initiatives (Poulin & Pérez-Ponce de León, 2017), it is necessary to understand its full extent and nature in lakes, as well as its evolutionary origins and significance. This is only possible by undertaking wide ranging surveys of fish communities, in representative but randomly selected sets of lakes.…”
Section: Conservation Implicationsmentioning
confidence: 99%
“…structuring into genetic populations, has been increasingly resolved by molecular genetic analyses. It is now widely reported across most taxonomic groups, including fish and other freshwater taxa (Poulin & Pérez‐Ponce de León, ), and has led some to view SIPD as common and widespread (Bickford et al., ; Seehausen & Wagner, ; Vonlanthen et al., ). Arguably, this might be expected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation